Research on internal communication and cooperative learning communities in Chinese universities from the perspective of positive organizational behavior - Han Juan; Chiew, Tung Moi (Universiti Malaysia Sabah, 2024)
This study aims to explore the relationship between internal communication and cooperative learning communities in Chinese universities from the perspective of Positive Organizational Behavior (POB). In the context of China's society undergoing significant transformations, the demand for personal growth and societal transition from educational institutions has become increasingly crucial. Cooperative learning communities (CLC), as a collaborative learning approach adopted by the entire faculty and students based on predetermined organizational principles, are considered an effective mechanism for advancing educational quality and fostering comprehensive student development. Employing various methods, including surveys and teacher interviews, this research investigates the mutual influence and correlation between internal communication and cooperative learning communities in Chinese universities. Guided by the theory of POB, we examine the significance of internal communication and cooperative learning communities in shaping and developing the educational ecosystem of higher education institutions. Previous research findings demonstrate that internal communication from the perspective of POB plays a pivotal role in fostering the formation and stability of cooperative learning communities. Effective internal communication channels facilitate improved collaboration and knowledge-sharing among students, thereby enhancing their learning outcomes. Moreover, the active participation and support of teachers have positive effects on the establishment and maintenance of learning communities. Teachers promote positive interactions among students within the communities through encouraging collective learning and providing personalized guidance. Furthermore, the existence and development of CLC also yield positive impacts on POB. These communities create a positive learning environment for students, enhancing their learning motivation and self-efficacy. The application of POB theory plays a critical role in the construction of CLC within higher education institutions. In conclusion, this study delves into the relationship between internal communication and cooperative learning communities in Chinese universities from the perspective of POB. It explores the formation and operational mechanisms of CLC, contributing valuable theoretical and practical insights for optimizing educational management, nurturing comprehensive student development, and advancing the overall development of higher education institutions.